Glycogen as a biodegradable construction nanomaterial for in vivo use - Filippov, Sergey K; Sedlacek, Ondrej; Bogomolova, Anna; Vetrik, Miroslav; Jirak, Daniel; Kovar, Jan; Kucka, Jan; Bals, Sara; Turner, Stuart; Stepanek, Petr; Hruby, Martin (Macromolecular bioscience, 2012)
It is demonstrated that glycogen as a biodegradable and inexpensive material coming from renewable resources can be used as a carrier for the construction of in vivo imaging nanoagents. The model system considered is composed of glycogen modified with gadolinium and fluorescent labels. Systematic studies of properties of these nanocarriers by a variety of physical methods and results of in vivo tests of biodegradability are reported. This represents, to the authors' best knowledge, the first such use of glycogen.
Keywords: gadolinium; heterocyklické sloučeniny; Glycogen; Gadolinium; Drug Delivery Systems; Nanostructures; Organometallic Compounds; zvířata; Fluorescence; nanostruktury; organokovové sloučeniny; Biocompatible Materials; lékové transportní systémy; Heterocyclic Compounds; transmisní elektronová mikroskopie; molekulární zobrazování; Microscopy, Electron, Transmission; fluorescence; biokompatibilní materiály; Animals; Molecular Imaging; glykogen